Prediction equation for the mini-mental state examination: influence of education, age, and sex - Liliane Patrícia de Souza Mendes; Fernanda Ferreira Malta; Thaís de Oliveira Ennes; Giane Amorim Ribeiro-Samora; Rosângela Corrêa Dias; Bianca Louise Carmona Rocha; Marina Rodrigues; Larissa Faria Borges; Verônica Franco Parreira (Universidade de São Paulo, 2019)
ABSTRACT The mini-mental state examination (MMSE) is a screening test used worldwide for identifying changes in the scope of cognition. Studies have shown the influence of education, age and sex in the MMSE score. However, in Brazil, the studies consider only one factor to score it. The aim of this study was to establish a prediction equation for the MMSE. An exploratory cross-sectional study was developed and trained researchers examined participants at the community. The volunteers were evaluated by the MMSE and also by the Geriatric Depression Scale (GDS). The MMSE score was the dependent variable. Age, educational level, sex, and GDS score were the independent variables. Multivariate regression analysis was used to determine the model of best prediction value for MMSE scores. A total of 250 participants aged 20-99 years, without cognitive impairment, were assessed. The educational level, age, and sex explained 38% of the total variance of the MMSE score (p<0.0001) and resulted in the following equation: MMSE=23.350+0.265(years of schooling)-0.042(age)+1.323(sex), in which female=1 and male=2. The MMSE scores can be better explained and predicted when educational level, age, and sex are considered. These results enhance the knowledge regarding the variables that influence the MMSE score, as well as provide a way to consider all of them in the test score, providing a better screening of these patients.